Pengaruh Literasi Keuangan dan Persepsi Risiko Terhadap Keputusan Investasi Generasi Z di Kota Bandung dengan Locus of Control Sebagai Variabel Moderasi - Edelways Riry Surya Palupi; Eka Yulianti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the influence of financial literacy and risk perception on investment decisions among Generation Z in Bandung City, with locus of control as a moderating variable. The research method used is a quantitative survey approach. The population in this study was Generation Z residents in Bandung City who had invested at least once. The total sample size was 100 respondents, determined through purposive sampling, with data obtained through online questionnaires. This study used moderated regression analysis with the assistance of SPSS version 26. The results showed that financial literacy has a positive influence on investment decisions, risk perception has a positive influence on investment decisions, locus of control moderates financial literacy on investment decision-making, financial literacy and risk perception jointly have a positive influence on investment decision-making, and locus of control moderates risk perception on investment decisions.